Estrutura da população e epidemiologia de Moniliophthora roreri no Magdalena Medio Colombiano - Jaimes Suárez, Yeirme Yaneth [UNESP] (2016)
Frosty pod rot disease (FPR) on cocoa, caused by Moniliophthora roreri, is one of the most devastating cocoa diseases in the Western Hemisphere, including the Magdalena Valley areas in Colombia, which is considered the possible center of origin for the species. We analyzed the genetic diversity of isolates from the states Santander, Antioquia, Tolima and Huila of Colombia using twenty-three simple sequence repeats (SSR) markers. In total, 117 different multilocus genotypes were found among 120 isolates, each one represented as a unique haplotype. The observed and standardized index of association (IA and řd) indicates that the populations of M. roreri are clonal populations. Furthermore, given the high haplotype diversity with linkage disequilibrium are suggest that M. roreri could be an asexual species possibly undergoing rare recombination or partial recombination due to parasexuality. Three geographical groups were recognized among the isolates using Bayesian clustering methods. Similar results were obtained after discriminant analysis of principal components (DAPC), principal coordinate analysis (PCA) and a neighbor-joining tree from microsatellite loci based on Nei distance. The identified clusters where explained by geographical differentiation and cacao clones and environmental variables did not contribute significantly to the genetic differentiation between groups. Regarding to the disease epidemiology, incidence of Frosty Pod Rot (FPR) disease, caused by Moniliophthora roreri, in time and space on clones with different level of resistance were investigated in four localities of Santander State between July 2013 and May 2015. Generalized linear model was used to analyze the temporal and spatial progress of FPR. Poisson distribution with logarithm link function was chosen because of data overdispersion. A significant interaction was found between clones and localities on epidemics parameters. The susceptible clone SCC61 had the higher levels of disease in the most localities, excepted in San Vicente where it obtained the lower level. The locality in San Vicente had the lower levels of disease in all cacao clones, when compared with the other localities. After applied Moran’s I test to data of cut disease pod in La Suiza Research Center, were evident in spatial autocorrelation. The dynamic study provide that FPR epidemics vary according to location and plant material and its location on the plot. The information obtained in this word could be used to improve the management of FPR at the regional level and the practices will be adjusted to local level considering microenvironmental variation.